Structural determinants of specificity and catalytic mechanism in mammalian 25-kDa thiamine triphosphatase - Delvaux, David; Kerff, Frédéric; Murty, Mamidanna R.V.S.; Lakaye, Bernard; Czerniecki, Jan; Kohn, Gregory; Wins, Pierre; Herman, Raphaël; Gabelica, Valérie; Heuze, Fabien; Tordoir, Xavier; Marée, Raphaël; et al. (Biochimica et biophysica acta, 2013)
Thiamine triphosphate (ThTP) is present in most organisms and might be involved in intracellular signaling. In mammalian cells, the cytosolic ThTP level is controlled by a specific thiamine triphosphatase (ThTPase), belonging to the CYTH superfamily of proteins. CYTH proteins are present in all superkingdoms of life and act on various triphosphorylated substrates. Using crystallography, mass spectrometry and mutational analysis, we identified the key structural determinants of the high specificity and catalytic efficiency of mammalian ThTPase. Triphosphate binding requires three conserved arginines while the catalytic mechanism relies on an unusual lysine–tyrosine dyad. By docking of the ThTP molecule in the active site, we found that Trp-53 should interact with the thiazole part of the substrate molecule, thus playing a key role in substrate recognition and specificity. Sea anemone and zebrafish CYTH proteins, which retain the corresponding Trp residue, are also specific ThTPases. Surprisingly, the whole chromosome region containing the ThTPase gene is lost in birds. The specificity for ThTP is linked to a stacking interaction between the thiazole heterocycle of thiamine and a tryptophan residue. The latter likely plays a key role in the secondary acquisition of ThTPase activity in early metazoan CYTH enzymes, in the lineage leading from cnidarians to mammals. We show that ThTPase activity is not restricted to mammals as previously thought but is an acquisition of early metazoans. This, and the identification of critically important residues, allows us to draw an evolutionary perspective of the CYTH family of proteins. [Display omitted] •CYTH proteins are present in all superkingdoms of life.•Animal CYTH proteins act as highly specific thiamine triphosphatases.•The specificity results from the interaction of thiamine with a tryptophan residue.•The catalytic mechanism relies on an unusual lysine–tyrosine dyad.•Thiamine triphosphatase activity is a secondary acquisition in early metazoans.